Implementing EU mobility partnerships : putting soft law into practice - Tittel-Mosser, Fanny (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Mobility partnerships between the EU and third countries are usually viewed as reflecting asymmetric power relations where development aid, trade relations and visa policies are made conditional upon the cooperation by third countries with an EU agenda of migration control. This book argues that three main factors condition the relevance of Mobility Partnerships: the state of relations between EU Member States and a third country, and in particular, to what extent postcolonial ties play a role here; the power of negotiation of a third country, which is linked to its geopolitical importance for the EU; and its administrative capacity, which is understood here as the capacity of a state to define and implement policies and to legislate and enforce the law. The work combines a comparative legal analysis of the development of the legal and policy frameworks in the two cases of Morocco and Cape Verde with an empirical study of the implementation of Mobility Partnerships' projects. The analysis demonstrates that Mobility Partnerships, despite their non-binding nature, have legal and policy relevance for these third countries with regard to the regulation of migration, asylum, human trafficking and even labour law. As such, this book makes a contribution to the understanding of the interplay between the interests of EU, Member State and third country actors in the implementation of the Mobility Partnerships"--
Introduction -- Mobility partnerships in the context of EU external-migration governance -- EU mobility partnerships with Cape Verde and Morocco : context of adoption, content and stage of implementation -- Legal and policy developments in Morocco and Cape Verde -- Contextualisation of the legal and policy developments in Morocco and Cape Verde -- Mobility partnerships : the way forward -- Conclusion.
Based on author's thesis (doctoral - Universidade do Minho, Escola de Direito, 2018) issued under title: The legal and policy relevance of EU mobility partnerships : a comparative study of Morocco and Cape Verde.
OCLC-licensed vendor bibliographic record.
Keywords: Emigration and immigration law -- European Union countries; European Union countries -- Foreign relations -- Law and legislation; European Union countries -- Foreign relations -- Morocco; European Union countries -- Foreign relations -- Cabo Verde; Morocco -- Foreign relations -- European Union countries; Cabo Verde -- Foreign relations -- European Union countries; LAW / General; LAW / Civil Rights; LAW / Comparative